Integrated Liquidity and Risk Management Strategy as a Driver of Bank Efficiency: A SEM-PLS Study on BRI - Amelia, Ratih; Amin Hou; Muhammad Fathoni; Dini Vientiany (Journal of Finance Integration and Business Independence, 2025)
This study seeks to examine the impact of bank liquidity on bank efficiency, utilizing risk management quality as a mediating variable at Bank Rakyat Indonesia in 2024. The study challenge arises from the significance of liquidity stability and efficient risk management in enhancing banking operating efficiency, particularly at BRI, which operates on a CASA-based funding model and possesses the largest credit portfolio in Indonesia. This research employs a quantitative methodology with an explanatory framework, utilizing secondary data derived from BRI's 2024 financial statements and evaluated through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that bank liquidity exerts a positive and significant influence on both risk management quality and bank efficiency, whereas risk management quality positively and significantly impacts efficiency. Also, RMQ has been shown to partially mediate the influence of liquidity on efficiency. These results show that good risk management and high liquidity are two important things that can help BRI's operations run more smoothly and make more money. This study suggests that integrated liquidity enhancement and risk management methods must be perpetually fortified to sustain bank performance and competitiveness in the evolving financial sector